Firm Value Response to Internal and External Corporate Governance in the Nigerian Stock Market - Esan, Oluwatosin Mary; Nwobu, Obiamaka; Adeyanju, Ibukunoluwa T; Adeyemi, Jesutofunmi O (Asian Economic and Financial Review, 2022)
The slow pace of firm valuation and the rising occurrences of fraud have been attributed in part to corporate governance. This research aims to educate the companies and their management who are capable of reversing the current pace to a much better pace. This study also aims to ascertain the firm value response to internal and external corporate governance using evidence from the Nigerian stock market, which covers the period from 2012 to 2019. To determine the response of firm value to the internal and external corporate governance mechanisms, two indexes were determined using the Principal Component Analysis (PCA), and data was sourced from the annual reports of the sampled firms listed on the Nigerian stock market. The variables used were firm value proxied by Tobin’s Q, and the internal corporate governance index composed of board independence, board meeting, board size, and board education; and then the external corporate governance index was represented by corporate disclosures, audit type, timeliness of reporting, and corporate governance code. The data was analyzed through a series of tests including the descriptive statistics, PCA, correlation matrix, and panel data static estimators, amongst others. The findings obtained from the analysis show that internal corporate governance has a positive and significant influence on firm valuation and that external corporate governance has a negative and insignificant influence on firm valuation.